Workload and Burnout Among Urban Delivery Couriers: Evidence from the Indonesian Logistics Sector - Doli Maulana Gama Samudera Lubis; Sairah Sairah; Ayudia Popy Sesilia (About the Journal, 2026)
The rapid expansion of the logistics industry has intensified job demands for courier workers, increasing their vulnerability to burnout. This study examines the relationship between workload and burnout among couriers at PT. JNE Express Main Branch in Medan, Indonesia. A quantitative correlational design was employed using total sampling, involving 93 couriers. Data were collected using a 29-item Workload Scale and a 32-item Burnout Scale based on Maslach’s framework. Reliability analysis indicated high internal consistency (α = .888 for workload; α = .928 for burnout). Pearson product–moment correlation analysis revealed a strong positive relationship between workload and burnout (r = .733, p < .001), with workload explaining 53.8% of the variance in burnout (r² = .538). Although descriptive findings indicated that both workload and burnout were at relatively low levels, the strong correlation suggests that even small variations within these low levels are associated with substantial increases in burnout, indicating a structurally sensitive relationship between job demands and employee well-being. This study contributes to the literature by demonstrating that workload operates as a dominant and multidimensional predictor of burnout within the underexplored courier sector, particularly in a developing country context. These findings extend the applicability of the Job Demands–Resources (JD-R) model by highlighting the sensitivity of burnout risk even under moderate demand conditions. Practically, the results underscore the importance of proactive workload management, as incremental increases in job demands may significantly elevate psychological risk.Pesatnya perkembangan industri logistik telah meningkatkan tuntutan kerja bagi kurir, yang berpotensi meningkatkan risiko burnout. Penelitian ini bertujuan untuk mengkaji hubungan antara beban kerja dan burnout pada kurir di PT. JNE Express Cabang Utama Medan. Penelitian ini menggunakan desain kuantitatif korelasional dengan teknik total sampling yang melibatkan 93 kurir. Data dikumpulkan menggunakan Skala Beban Kerja sebanyak 29 item dan Skala Burnout sebanyak 32 item yang diadaptasi dari kerangka Maslach. Hasil uji reliabilitas menunjukkan konsistensi internal yang tinggi (α = 0,888 untuk beban kerja; α = 0,928 untuk burnout). Analisis korelasi product moment Pearson menunjukkan adanya hubungan positif yang kuat antara beban kerja dan burnout (r = 0,733, p < 0,001), dengan beban kerja menjelaskan 53,8% varians burnout (r² = 0,538). Meskipun hasil deskriptif menunjukkan bahwa beban kerja dan burnout berada pada kategori relatif rendah, kekuatan korelasi tersebut mengindikasikan bahwa variasi kecil dalam tingkat beban kerja tetap berkaitan dengan peningkatan burnout yang signifikan, sehingga mencerminkan hubungan yang sensitif secara struktural antara tuntutan kerja dan kesejahteraan psikologis karyawan. Penelitian ini memberikan kontribusi dengan menunjukkan bahwa beban kerja merupakan prediktor dominan dan multidimensional terhadap burnout pada sektor kurir yang masih relatif kurang diteliti, khususnya dalam konteks negara berkembang. Temuan ini memperluas penerapan model Job Demands–Resources (JD-R) dengan menekankan sensitivitas risiko burnout bahkan pada kondisi tuntutan kerja yang moderat. Secara praktis, hasil penelitian ini menegaskan pentingnya pengelolaan beban kerja secara proaktif, karena peningkatan kecil dalam tuntutan kerja dapat secara signifikan meningkatkan risiko psikologis.